2006
DOI: 10.1111/j.1440-1681.2007.04536.x
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous Nitric Oxide Attenuates Β‐adrenoceptor‐mediated Relaxation in Rat Aorta

Abstract: 1. Divergent evidence suggests that the intracellular signalling pathways for beta-adrenoceptor-mediated vascular relaxation involves either cAMP/protein kinase (PK) A or endothelial nitric oxide (NO) release and subsequent activation of cGMP/PKG. The present study identifies the relative roles of NO and cAMP, as well as dependence on the endothelium for beta-adrenoceptor-mediated relaxation of rat isolated aortas. 2. Cumulative concentration-response curves to isoprenaline (0.01-3 micromol/L) in phenylephrine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…Indeed, NO can reduce cAMP as observed in rat aorta (Kang et al . ); similarly, prostanoid‐induced activation of the EP3 receptor (one of the prostaglandin receptors) leads to a decrease in cAMP (Hatae et al . ).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, NO can reduce cAMP as observed in rat aorta (Kang et al . ); similarly, prostanoid‐induced activation of the EP3 receptor (one of the prostaglandin receptors) leads to a decrease in cAMP (Hatae et al . ).…”
Section: Discussionmentioning
confidence: 99%
“…31) Recently, it has also been reported that b-adrenoceptors induce vascular smooth muscle relaxation by acting through the NO-cGMP pathway and, when that is disrupted by endothelium removal or the presence of an NO synthase inhibitor, the cAMP pathway in smooth muscle is used. 32) To the best of our knowledge, there is no previous data on the eŠects of ALA on ACh-and ISO-induced relaxations in rat aorta. It is reported that ALA is a potent antioxidant for the protection of the vascular wall against oxidative injury associated with diabetes mellitus.…”
Section: Discussionmentioning
confidence: 99%
“…Compatible with these findings is that inhibition of nitric oxide synthase modestly decreased relaxation to β -AR agonists [102]. Therefore, endothelium- and vascular smooth muscle-mediated function may be additive in that β -AR-mediated vasorelaxation appears to be induced via both nitric oxide-mediated pathways (endothelial), and cAMP-mediated pathways (vascular smooth muscle) [103]. …”
Section: Age-related Changes In Vascular Functionmentioning
confidence: 99%